Staging the Dead Journal for Religion, Film and Media - Anna-Katharina Höpflinger (Journal for Religion, Film and Media, 2015)
The body is one of the basic media that form and communicate gender. How important gender is for the perception of an individual becomes especially clear by looking at the exhibition of a dead body. Having nothing left other than the body, the deceased are reduced to characteristics that seem to be the basis of a specific culture. However, in religious contexts the exhibition of mortal remains can also be used to overcome gender differentiations. In this article, I will focus on Central Europe, and argue that material presentations are an authoritative means of forming concepts of gender and religion.